Conservation Agriculture for Managing Degraded Lands and Advancing Food Security in North Eastern Region of India - Das, Anup; Babu, Subhash; Layek, Jayanta; Devi, M. Thoi Thoi; Krishnappa, R.; Ghosh, P. K.; Prakash, N.; Ngachan, S. V. (International Journal of Economic Plants, 2017)
Hill and mountainous landscape and physiography are prone to accelerated water runoff, soil erosion, sedimentation, and non-point source pollution. Ecological restoration of degraded hill lands would trigger the process of soil/terrestrial C sequestration, improvements in productivity and use efficiency of inputs, mitigation and adaptation of climate change, provisioning of essential ecosystem services, increase in biodiversity by restoration of wildlife habitat, and increase in human wellbeing. The North Eastern Region (NER) of India (26.2 M ha geographical area), comprises the states of Arunachal Pradesh, Assam, Manipur, Meghalaya, Mizoram, Nagaland, Sikkim and Tripura, lies between 22005’ and 29030’ N latitudes and 87055’ and 97024’ E longitudes. The region is characterized by diverse agro-climatic and geographical situations. On steep slope, because of continuous removal of topsoil, organic matter status is poor to medium. In this region, around 56% of the area is under low altitude, 33% mid altitude and the rest under high altitude. Reversing degradation trends necessitates identification and implementation of site-specific strategies. Choice of strategies depends on biophysical (climate, geology, soil type, drainage patterns, vegetation, land use) and human factors (demography, infrastructure, land tenure, access to credit and market). There is an urgent need to formulate a regional program in a mission mode approach engaging all the stakeholders to disseminate CA approaches for food and environmental security in the region. Need based technical support, farm mechanization, credit facilities and other inputs should be made available to the farmers to achieve desired goal of food security and environmental sustainability.